-5f=-5-4f

Simple and best practice solution for -5f=-5-4f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5f=-5-4f equation:



-5f=-5-4f
We move all terms to the left:
-5f-(-5-4f)=0
We add all the numbers together, and all the variables
-5f-(-4f-5)=0
We get rid of parentheses
-5f+4f+5=0
We add all the numbers together, and all the variables
-1f+5=0
We move all terms containing f to the left, all other terms to the right
-f=-5
f=-5/-1
f=+5

See similar equations:

| 4^x-3.3=5x+12.2 | | h-187=341 | | -n+4=-2n-3 | | -10=14x+14 | | 8x-15=31 | | 3i-9=15 | | x+86+x=90 | | -7u-9=-6u | | 8x-1+6x=11 | | 30x+14+10x+16=180 | | 10i-24=85 | | 6a-(5-a)=3a-25 | | 6i-4=50 | | 7p-(3p+4=-2(2p-1)+10 | | (x+24)+x=180 | | 7i-3=-73 | | 9i-4=-76 | | (x+34)+x=90 | | 9i-3=-84 | | 11y-(2y-8)=89 | | (29x)+x=180 | | 4(7x=6)=80 | | 16+32x=20x | | 5b^2+2=23b | | 4(i-3)=5 | | 100+5x+10=180 | | 41.4=3.6(i+4.5) | | (x+74)+x=90 | | 11-9m=-16 | | 32=x-21 | | 2x+5+3x-15=5x | | 8.5k+7.5k=11 |

Equations solver categories